Utilization and Types of Laboratory Approaches Employed in Public Secondary Schools in Ilocos Norte - Dalere, Johanna Justine; Calzada, Marc Paul T. (Future Science / FSH-PH Publications, 2025)
This study investigates the laboratory practices of science teachers in public secondary schools within the Schools Division of Ilocos Norte, focusing on the types of laboratory teaching approaches employed and their frequency of use. Utilizing a quantitative research design, data were collected through surveys to assess the extent of implementation of various methodologies, including Demonstration, Guided Inquiry, Open Inquiry, Structured Inquiry, and Confirmation Inquiry. The analy-sis revealed a significant correlation between the types of approaches used and their frequency of implementation, with Demonstration and Guided Inquiry being the most frequently employed methods. In con-trast, Open Inquiry and Confirmation Inquiry were utilized less often, indicating potential barriers to their implementation. The findings highlight the need for targeted professional development to enhance teachers' confidence and skills in employing a wider range of inquiry-based approaches. This research contributes valuable insights into the current state of laboratory practices in science education, emphasizing the importance of understanding these practices to inform future train-ing and support initiatives aimed at improving science instruction and fostering a more effective learning environment for students. Further research is recommended to explore the impact of these teaching ap-proaches on student learning outcomes and to identify challenges faced by teachers in implementing diverse laboratory methodologies.